Ball Hawks : The Arrival and Departure of the NBA in Iowa - Harwood, Tim, 1981- (Book collections on Project MUSE., 2018)
"The National Basketball Association has evolved dramatically from the circuit originally formed by the merger of the National Basketball League and the Basketball Association of America in 1949. The Waterloo Hawks - the only major league team in Iowa's history - took the court that winter as modern professional basketball was starting toward a still uncertain future. Ball Hawks; The Arrival and Departure of the NBA in Iowa, describes how Waterloo happened to be on hand at this moment in the sport's history and why the city was ultimately left behind after a short stay"--